Congratulations to Academician Lin Qun on His 70th Birthday (Journal of Computational Mathematics, 2006)
This special issue of the Journal of Computational Mathematics is dedicated to Professor Qun Lin, an outstanding mathematician and a Member of Chinese Academy of Sciences (CAS), on the occasion of his seventieth birthday.